THE AETIOLOGY OF THE INEFFICIENCY SYNDROME IN THE INDIAN POWER SECTOR : Main Issues and Conclusions of a Study - Kannan, KP and Vijayamohanan Pillai, N (Centre for Development Studies-WP324, 2002)
The present study is an attempt at a detailed diagnosis of the accumulated inefficiency in the Indian power sector, the consequent reform drives, and the political economy involved in these aspects. The discussion in the wider canvas of the national scenario is substantiated by focusing on the Kerala power sector, taken for illustrative purpose. It is shown that much of the capacity/energy deficit we experience today could be easily avoided with some achievable functional improvement in the power sector. We also estimate, on some very plausible assumptions, the avoidable cost of inefficiency at a few amenable functional levels and find it to represent about one-third of the reported cost of electricity supply in India in 1997-98! Given such scope for cost reduction, the attempts at tariff hikes amount to transferring the inefficiency onto the customers. Based on these observations, we argue that the present system predicament is due to problems that are just internal to the system. This then implies that there do remain sufficient quarters for remedial exercises, meant to remove the problems that stand in the way of the SEBs' improved performance. In other words, what the system badly requires is essence-specific reforms, not structure-specific ones. We hence question the (unfounded) logic of the structural reform in the sector now posited as the panacea. We also list out a number of feasible suggestions for the improved performance of the sector, in the context of Kerala.